Challenges of using digital technologies in audit - Vuković, Bojana; Tica, Teodora; Jakšić, Dejan (Anali Ekonomskog fakulteta u Subotici, 2024)
Every company must consider the changes in a digital environment. In the era of digital transformation, the company understands the importance of information technologies, and makes adjustments in the form of structural changes. Modern technology usage provides the possibility of the analysis of previously unimaginable types and amounts of data, and introduces significant changes in the field of auditing. By simplifying the audit work, digitalization has also created new opportunities for IT auditing. The aim of this paper is to present the opportunities and challenges of key digital trends in auditing, or the usage of big data analytics, artificial intelligence, blockchain technology, and robotic process automation. There is an emerging need for auditors to take advantage of digital technology usage and respond to the challenges of digitalization in a systematic and quality way. The progress of using digital technologies in auditing is contributing to more reliability and better quality reporting, which is leading to increased trust among stakeholders in the results of audit work.